Digital culture and tourism: Perception of landscape culture and distribution of homestay - Yuegang Chen; Yuting Pan; Yuxin Chen; Yan Wu (Amfiteatru Economic, 2025)
This research explores how landscape cultural perception impacts the spatial distribution of homestay businesses, and highlights the increasing role of digital technology in enhancing cultural tourism experiences and optimizing homestay industry operations. Using grounded theory, the research gets a relationship matrix to explore the theoretical logic between landscape resources and cultural perceptions, and then based on the S-O-R model, a theoretical framework is constructed to explain the impact of landscape culture perception on the distribution of homestays. The research also applies an empirical approach to analyse how cultural perceptions of landscape play in shaping the homestay distribution in Yangtze River Delta China. Additionally, digital platforms are found to enhance tourists' cultural perceptions and streamline their booking experiences, while providing homestay operators with effective tools for personalised marketing and operational efficiency.
Keywords: R12; Z32; C21; 330; digital culture and tourism; spatial distribution of homestays; perception of landscape culture; traffic accessibility; digital platform; grounded theory; ridge regression